Experience of Women after Immediate Postpartum Insertion of Intrauterine Contraceptive Device (PPIUCD), a Long-Acting Reversible Contraception - Fauzia Ali; Tazeen Fatima Munim; Shabnum Nadeem; Aisha Khatoon; Zubaida Masood (KARACHI MEDICAL AND DENTAL COLLEGE, 2022)
ABSTRACT Objective: To assess the experience (during and post procedure) of women after immediate postpartum and post placental Insertion of intrauterine contraceptive device (IUCD), a long acting reversible contraceptive (LARC). Methods: This prospective and longitudinal study was conducted during February 2019 to September 2019 in Gynae and Obstetrics department Unit 1 at Abbasi Shaheed Hospital. All 141 booked and non-booked patients who delivered in the hospital and received immediate postpartum intrauterine contraceptive device (PPIUCD),either post placental, intra cesarean or within 48 hours after delivery were included in the study regardless of the mode of delivery either intra-cesarean or spontaneous vaginal delivery. Written consent was taken for the contraceptive device insertion and verbal consent was taken to fill the proforma which included basic demographic information, their overall experience with postpartum intrauterine contraceptive device. Immediate experience was measured by assessing the pain during procedure and post insertion period. Further all participants were followed at six weeks and 6 months to collect information about any complains removal of IUCD and overall experience. Results: The mean age was 27.3 years with a standard deviation (SD) of 4.42. Among all the participants, 77(54.6%) had Cesarean section and 64(45.4%) had vaginal delivery. During procedure only 5(3.5%) had complain of mild pain and no immediate post procedural complains was recorded.  86(73.5%) participants at 6 weeks and 78(69.03%) participants at 6 months had no complained. Overall experience was found satisfactory in 86(73.5%) participants. Conclusion: Postpartum intrauterine contraceptive device (PPIUCD) provided satisfactory experience to majority of the women. So we recommend its use for better maternal and child health.